Studies of the behavior of wooden beams with a fire firebiodefence - Pozdeev Сергей; Gorbachenko Яна; Nekora Ольга; Kropiva Михаил (Vestnik of the Institute for Command Engineers of the MES of the Republic of Belarus, 2015)
Article is devoted to the behavior of wooden beams with fire protection in case of fire. The results of calculations of the rate of charring fragments of wooden beams with fire protection.